Is Jamie Oliver “Easy Peasy” in Slovene? - Metka Lovrin (ELOPE, 2013)
The research aims to identify the idiolectal features in selected cookbooks by Jamie Oliver (The Naked Chef, Happy Days with the Naked Chef and Jamie’s Ministry of Food), and how they were rendered into Slovene by Oliver’s translators. As a theoretical basis, it relies on Koller’s three-stage model for analyzing the original and the translation. The paper also confronts the problems that arise from cultural differences between Slovene and British culture. Lexical items are layered into independent categories in the form of concentric circles to denote quantity, significance and interconnection. Within these layers, I focus on specific analysis of expressions under the influence of word-formation, pop culture, gender specific language, onomatopoeia, phonetic symbolism, deliberate inaccuracy, comparison, informal and colloquial language, and creative instances such as “the icky factor”, “childish intimacy” and “the Peter-Pan-syndrome”. The translator’s subjective point of view was also taken into consideration.